2012
DOI: 10.1186/1477-7819-10-27
|View full text |Cite
|
Sign up to set email alerts
|

Histological features of the gastric mucosa in children with primary bile reflux gastritis

Abstract: BackgroundBile reflux is one of the primary factors involved in the pathogenesis of gastric mucosal lesions in patients with chronic gastritis; however, little is known about the exact histological features of bile reflux and its contributions to gastric mucosal lesions in this disease, especially in children with primary bile reflux gastritis (BRG). The aim of this study was to investigate the classic histological changes of the gastric mucosa in children with primary BRG.MethodsThe Bilitec 2000 was used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
0
18
0
2
Order By: Relevance
“…17 However, no consensus establishing objective, quantitative diagnostic criteria has been published. Thus, the morphologic characteristics defining FH in children with H. pylori gastritis 11 and with non-H. pylori gastropathy (NHPG) [18][19][20][21] are not congruent. This study applies an objective, reproducible approach, previously utilized to characterize FH in adult endoscopic biopsies, 22,23 to analyze pediatric H. pylori and NHPG tissue.…”
Section: Introductionmentioning
confidence: 99%
“…17 However, no consensus establishing objective, quantitative diagnostic criteria has been published. Thus, the morphologic characteristics defining FH in children with H. pylori gastritis 11 and with non-H. pylori gastropathy (NHPG) [18][19][20][21] are not congruent. This study applies an objective, reproducible approach, previously utilized to characterize FH in adult endoscopic biopsies, 22,23 to analyze pediatric H. pylori and NHPG tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In line with Rutledge et al's findings, no EGJ function and motility abnormalities were observed after OGB. In addition, for the first time we documented a drastic reduction not only in esophageal acid exposure time but also in all kinds of refluxes (acidic, weakly acidic, and (3)(4)(5) .000 26 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) 38 .000 Recumbent 9 (2-16) 0 (0-2) .000 7 (4-9) 15 (10)(11)(12)(13)(14)(15)(16)(17) .000 Acid reflux pattern at MII Total 32 (15-50) 3 (3)(4)(5)(6) .000 12 (9)(10)(11)(12)(13)(14) 16 (9--18) .000 Upright 27 (13-37) 3 (3)(4) .008 9 (8-10) 13 (7)(8)(9)(10)(11)(12)(13)(14)…”
Section: Discussionmentioning
confidence: 94%
“…Although duodenogastric bile reflux is a physiologic phenomenon [19,20], excessive duodenogastric biliary reflux can lead to intestinal metaplasia, esophageal mucosal damage, symptomatic gastritis/ esophagitis, Barrett's esophagus, and gastric/esophageal cancer [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Было показано, что фовеолярная гиперпла-зия коррелирует с выраженностью билиар-ного рефлюкса и служит гистологической характеристикой первичного рефлюкс-гас-трита у детей [5].…”
Section: Morphological Characteristics Of Reflux Gastritisunclassified
“…В ряде исследова-ний показано, что фовеолярная гиперпла-зия -гистологическая характеристика реф-люкс-гастрита [5]. По другим данным, не было выявлено корреляционной связи меж-ду степенью выраженности этого признака и количеством, а также продолжительностью жёлчных рефлюксов в желудке [8].…”
unclassified